2021
DOI: 10.1038/s41598-021-02426-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vaginal douching products on vaginal Lactobacillus, Escherichia coli and epithelial immune responses

Abstract: We compared the effect of commercial vaginal douching products on Lactobacillus crispatus, L. jensenii, L. gasseri, L. iners, E. coli, and immortalized vaginal epithelial cells (VK2). All studied douching products (vinegar, iodine and baking soda based) induced epithelial cell death, and all inhibited growth of E. coli. Co-culture of vaginal epithelial cells with any of the lactobacilli immediately following exposure to douching products resulted in a trend to less human cell death. However, co-culture of epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Specifically, washing practices are associated with BV acquisition and reduced Lactobacillus abundance ( 67 , 68 ). In one study investigating the effect of vaginal hygiene products on vaginal microbiome found Lactobacillus growth was not inhibited when using vinegar and iodine based products ( 69 ). Instead of directly inhibiting bacterial growth, these products induced epithelial cell death and proinflammatory response in vitro , marked by increased interleukin (IL)-6 and IL-1β.…”
Section: Host Factors Determining Vaginal Microbial Communitymentioning
confidence: 99%
“…Specifically, washing practices are associated with BV acquisition and reduced Lactobacillus abundance ( 67 , 68 ). In one study investigating the effect of vaginal hygiene products on vaginal microbiome found Lactobacillus growth was not inhibited when using vinegar and iodine based products ( 69 ). Instead of directly inhibiting bacterial growth, these products induced epithelial cell death and proinflammatory response in vitro , marked by increased interleukin (IL)-6 and IL-1β.…”
Section: Host Factors Determining Vaginal Microbial Communitymentioning
confidence: 99%
“…Both organs (vulva and vagina) can absorb arsenic, although, anatomically, the vagina absorbs faster. The previous studies demonstrate that arsenic absorbed through the vagina and vulva is distributed more efficiently and effectively than the oral route [12], [27].…”
Section: Discussionmentioning
confidence: 99%
“…These products are applied by sticking them to the vulva or smeared and douching through the vagina. These products' harmful active substances enter and are absorbed by the vagina when the vulva is submerged for a long time or through the vaginal douching process [12].…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal douching is a method of flushing a product through the vagina, often as an attempt to address vaginal discomfort or discharge. An in vitro 2021 study found that the contents of common commercial douching products (vinegar, iodine and baking soda) all may be associated with epithelial inflammation and disruption of the anti-inflammatory effects of lactobacilli ( 140 ). It is hypothesized that increased inflammation may inhibit recolonization of beneficial lactobacilli.…”
Section: Complementary and Alternative Optionsmentioning
confidence: 99%